2010
DOI: 10.1016/j.pnpbp.2010.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Novel positive allosteric modulators of GABAA receptors: Do subtle differences in activity at α1 plus α5 versus α2 plus α3 subunits account for dissimilarities in behavioral effects in rats?

Abstract: Over the last years, genetic studies have greatly improved our knowledge on the receptor subtypes mediating various pharmacological effects of positive allosteric modulators at GABA A receptors. This stimulated the development of new benzodiazepine (BZ)-like ligands, especially those inactive/low-active at GABA A receptors containing the α 1 subunit, with the aim of generating more selective drugs. Hereby, the affinity and efficacy of four recently-synthesized BZ site ligands: SH-053-2'N, SH-053-S-CH3-2'F, SH-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
55
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 43 publications
(65 citation statements)
references
References 41 publications
(75 reference statements)
9
55
1
Order By: Relevance
“…The drug was then brought to a final concentration of 0.1 mg/kg in 50% propylene glycol and 50% deionized water for systemic administration (i.v.). The 1 mM concentration of SH-053-2 0 F-R-CH3, used for local infusion into the ventral HPC, has been demonstrated in competition binding assays to provide optimal binding to the a5 subunit of the GABA A receptor with little nonspecific binding at the other alpha (1-3) subunits (Savic et al, 2010). Local infusions were performed in anesthetized animals before electrophysiological recordings.…”
Section: Sh-053-2 0 F-r-ch3 Preparation and Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The drug was then brought to a final concentration of 0.1 mg/kg in 50% propylene glycol and 50% deionized water for systemic administration (i.v.). The 1 mM concentration of SH-053-2 0 F-R-CH3, used for local infusion into the ventral HPC, has been demonstrated in competition binding assays to provide optimal binding to the a5 subunit of the GABA A receptor with little nonspecific binding at the other alpha (1-3) subunits (Savic et al, 2010). Local infusions were performed in anesthetized animals before electrophysiological recordings.…”
Section: Sh-053-2 0 F-r-ch3 Preparation and Treatmentmentioning
confidence: 99%
“…In the present study, we use the MAM model to demonstrate the effectiveness of a novel compound, SH-053-2 0 F-R-CH3, in restoring normal HPC activity and secondary spontaneous DA activity. SH-053-2 0 F-R-CH3 is unique as a benzodiazepine-positive allosteric modulator (PAM) selective for the a5 subunit of the GABA A R (Cook et al, 2009;Fischer et al, 2010;Savic et al, 2010). Furthermore, the efficacy of a5GABA A R PAM treatment in reducing the hyperlocomotor response of MAM animals to amphetamine is explored.…”
Section: Introductionmentioning
confidence: 99%
“…Taken together, this research of the S-CH 3 enantiomers has provided several novel ligands that possess good safety and metabolic profiles for further in vivo behavioral testing in animal models in both schizophrenia and depression. [23][24][25][31][32] The in vivo activity of 8c and 9a in models of schizophrenia and depression is ongoing and preliminary studies look very promising.…”
Section: Discussionmentioning
confidence: 99%
“…Since 1 and 2 both target the α5-subunit, they have been assayed in several behavioral models. Examination of the results revealed that 2 exerted anxiolytic effects in both rhesus monkeys 31 and rats, 32 while 1 had only a minimal anxiolytic effect when much higher doses were applied. Interestingly, 2 also successfully mitigated the amphetamine-induced hyperactivity in a poly (I:C) animal model of schizophrenia.…”
Section: -2'f-r-chmentioning
confidence: 99%
See 1 more Smart Citation